MSHE-PWM harmonic suppression method of mine hoist active front end - WAN Jun; WANG Yu; WEN Xiaofei (Gong-kuang zidonghua, 2015)
In view of problem of harmonic pollution and system loss of active front end of 10 kV high voltage mine hoist, MSHE-PWM harmonic suppression method was proposed. ANPC five-level topology mathematical model was established to analyze MSHE-PWM harmonic suppression principle and solve MSHE-PWM nonlinear equations under constraint conditions. Voltage balance control method of suspended capacitor was also given. The results of MSHE-PWM performance test based on 1 MW industrial prototype show that SHE-PWM technology achieves grid side low-order harmonic control of 10 kV high voltage mine hoist, and comparison experiment with SV-PWM further demonstrates superiority of MSHE-PWM in solving problems of temperature-rise and loss of 10 kV high voltage inverter system.